2010
DOI: 10.1007/s12011-010-8889-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium Level is Negatively Associated with Fasting Serum Glucose Level in Korean Adults

Abstract: Several studies have observed an inverse association between serum magnesium and fasting glucose levels. However, there have been sparse data on Koreans. The present study was designed to evaluate the association between serum magnesium and fasting serum glucose levels in Korean adults. A total of 949 Korean adults who visited an outpatient at a university hospital were included in this study. We compared mean values of clinical data according to the tertile of serum magnesium level using analysis of covarianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
2
4
0
1
Order By: Relevance
“…We have also observed an association between glucose and Mg, which confirms the results of other studies [32, 33]. In this study, we observed following supplementation that there were increased concentrations of Mg associated with decreased levels of glucose in the serum of the GTE group.…”
Section: Discussionsupporting
confidence: 92%
“…We have also observed an association between glucose and Mg, which confirms the results of other studies [32, 33]. In this study, we observed following supplementation that there were increased concentrations of Mg associated with decreased levels of glucose in the serum of the GTE group.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, in most normal adults, serum magnesium ranges from 0.70 to 1.10 mM/L. In Korea, there was a few report about magnesium status of normal population or pregnant women, Song et al reported that the magnesium levels of these subjects including type 2 diabetes patients are 0.85±0.07 mM/L, respectively (18). However, the National Academy of Science and the Institute of Medicine have reported that an estimated 50%-85% of the US population has subclinical or severe magnesium deficiency (19).…”
Section: Discussionmentioning
confidence: 99%
“…Mg may play a key role in the regulation of carbohydrate and lipid metabolism (44,45). Severe magnesium deficiency can promote lipogenesis (5,29,41).…”
Section: Discussionmentioning
confidence: 99%